Effect of different velocity loss thresholds during a resistance training program on jump and sprint performances in trained female athletes - Hiroki Kambara; Kazuhiro Sakamoto; Yuya Watanabe; Mitsuo Neya (PLoS ONE, 2026)
This study aimed to explore the effects of velocity-based resistance training (VBT) using different velocity loss (VL) thresholds on jump and sprint performance in trained female athletes. Fifteen college-level female basketball players completed an 8-week VBT program (2 sessions/week), involving parallel back squats performed at a target mean propulsive velocity of 0.7 m/s. Participants were randomly assigned to two groups: VL10% (n = 8) and VL20% (n = 7), where training sets were terminated when the target velocity-loss threshold was exceeded for the second time within the same set. Performance tests, including one-repetition maximum (1RM), squat jump (SJ), countermovement jump (CMJ), and 20-m sprint (SP20) with split times recorded at 5 m (SP5) and 10 m (SP10), were conducted pre- and post-intervention. The VL10% group showed significant improvements in SJ (p = 0.048, d = 1.30), SP10 (p = 0.004, d = 0.62), SP20 (p = 0.002, d = 0.67), and 1RM (p = 0.002, d = 0.29). The VL20% group also showed improvements in SP10 (p = 0.004, d = 0.42), SP20 (p = 0.002, d = 0.56), and 1RM (p = 0.002, d = 0.62), although SJ did not significantly improve. Despite no significant interaction effects, effect sizes suggest possible differences that require verification in adequately powered trials. VBT using low VL thresholds may be useful for maintaining movement velocity with lower training volume; however, between-group differences were not statistically significant and CMJ did not show clear improvement. Larger-scale studies are needed to confirm these trends.